Endodontic treatment of birradicular maxillary canine: case report - Castro-Núñez, Gabriela Mariana [UNESP]; Kuga, Milton Carlos [UNESP]; Escalante-Otárola, Wilfredo Gustavo [UNESP] (Dental Press International, 2020)
This paper describes an unusual case of right maxillary canine with two roots. This is the fourth finding that has been reported in the literature. A 66-year-old female patient was referred to endodontic treatment in the tooth #13. Clinical evaluation showed that tooth #13 presented no response after the vitality test. Radiographs were taken and revealed that the tooth #13 presented two roots. Then, the patient was submitted to endodontic treatment. This case report is relevant because it describes an atypical anatomical variation, but with possible occurrence in endodontic clinical. For this reason, the dentist needs to have knowledge of the normal anatomy of the teeth to correctly perform the endodontic treatment, as well as to know the possible anatomical variations, and to thoroughly analyze the diagnostic radiography to have an individualized notion of the anatomy of the tooth to be treated.
Keywords: Endodontics; Root canal obturation; Root canal therapy